Decision Support System for Employee Performance Evaluation with Promethe Method. Case Study: Faculty of Engineering, Pancasila University - Sri Rezeki Candra Nursari; Amir Murtako (Komunitas Dosen Indonesia, 2021)
High competent human resources can support the level of employee performance. By conducting performance evaluation assessments it will be known the achievements of each employee. Assessment of employee performance evaluation carried out by the Faculty of Engineering, University of Pancasila uses criteria of diligence, teamwork, sincerity to work, skills, initiative, independence and attendance. The weights of criteria still determined by the Faculty authority. In this study, the authors used the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) to assist in making employee performance evaluation decisions, so that it can be seen which employees get the reward with good performance. There are six stages of the ranking including determine criteria and its weights, calculating the values of the requirements for each employee, preference value calculation between alternatives, calculating the value for the index, calculating entering flow, leaving flod and net flow. The data used is in the form of employee performance evaluation data that have range of 5 years consist of 16 samples taken from employee data from Faculty of Engineering, University of Pancasila. The calculation have been made using this six stages of the PROMETHEE method and after evaluation using precision approach have performance result of 96,364% accuracy compared with the conventional method